1987
DOI: 10.1901/jeab.1987.48-277
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Conditional Discrimination Learning by Pigeons

Abstract: In Experiment 1 (within subjects) and Experiment 2 (between subjects) it was shown that the sequential training of pigeons on a color discrimination and then on its reversal, each in a different floor-tilt/ texture context, failed to produce conditional control of discriminative performance by those contexts. Daily alternation between the two problems (with correlated contexts) was successful, however. In each of these experiments conditional control was better reflected in generalization test performance in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The acquisition of a conditional discrimination may be facilitated by the use of a procedure in which conditional control is explicit in the sense that the use of the conditional cues facilitates the mastery of the task. Thomas, Stengel, Sherman, and Woodford (1987) recently showed that floor tilt and texture cues may gain conditional control over discriminations based upon key color via the use of a CSDR procedure, although extensive training with the single reversal procedure was ineffective with these cues. This result is in contrast to that reported by Thomas and Goldberg (1985), who found no difference between single reversal and CSDR procedureswhenhouselight and key-eolor cues were used.…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of a conditional discrimination may be facilitated by the use of a procedure in which conditional control is explicit in the sense that the use of the conditional cues facilitates the mastery of the task. Thomas, Stengel, Sherman, and Woodford (1987) recently showed that floor tilt and texture cues may gain conditional control over discriminations based upon key color via the use of a CSDR procedure, although extensive training with the single reversal procedure was ineffective with these cues. This result is in contrast to that reported by Thomas and Goldberg (1985), who found no difference between single reversal and CSDR procedureswhenhouselight and key-eolor cues were used.…”
Section: Resultsmentioning
confidence: 99%
“…In the original study by Thomas et al (1981, Experiment 2), approximately 2.5 hr of training time was sufficient. In recent experiments using floor tilt and key color cues (see Thomas, Stengel, Sherman, & Woodford, 1987) and houselight and auditory frequency cues (see Thomas, Curran, & Russell, 1988), even extensive single reversal training failed to produce evidence of conditional control. One reason is certainly the extreme salience of both the houselight and key color cues used in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Experiment 2 demonstrated that the frequent switching between boxes in Phase 1, designed to invalidate any differences between them as potential retrieval cues, had no noticeable effect on the size of the context-specificity effect. Thomas and Goldberg (1985) had previously shown no significant effect of frequent switching between houselight and tone versus no-houselight and white-noise context, but Thomas et al (1990) and Thomas et al (1987) had shown that frequent switches are essential to establish conditional control by some less salient contextual stimuli. This suggests that the box cues, signaling different locations in the world, are extremely salient to pigeons, despite the fact that the actual cues utilized are not apparent to human observers.…”
Section: Methods Subjects and Apparatusmentioning
confidence: 99%
“…It is well established that conditional discrimination training may be facilitated by providing subjects with frequent and repeated alternations of conditional cues (see Thomas, Cook, & Terrones, 1990;Thomas, Stengel, Sherman, & Woodford, 1987), and in the case of cues that are not very salient, such alternations may be essential. Experiment 2 was performed to test the role of frequent switches between chambers in the initial phase of training.…”
Section: Apparatusmentioning
confidence: 99%